2020
DOI: 10.1038/s41598-020-60847-0
|View full text |Cite
|
Sign up to set email alerts
|

Initial decrease in the ambient dose equivalent rate after the Fukushima accident and its difference from Chernobyl

Abstract: In 2011, after the Fukushima Dai-ichi Nuclear Power Plant accident, the initial decrease in the ambient dose equivalent rate (dH*(10) dt−1), an alternative quantity to the effective dose, was studied using monitoring data obtained from March 16, 2011. The dH*(10) dt−1 was normalized by the 137Cs activity per unit area (norm-dH*(10) dt−1) to analyze the data across monitoring sites with different deposition levels. The norm-dH*(10) dt−1 showed a rapid decrease during the first 60 days, followed by slow decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…Recent studies have also suggested that anthropogenic activities can promote reduced air dose rate (Saito et al, 2019;Nakama et al, 2019;Yoshimura et al, 2020), indicating their importance in controlling the radiocesium levels on the ground and their effect on variation and temporal change of the RF. Radiocesium activity was monitored in atmospheric aerosol samples collected at 11 sites for five months after the FDNPP accident as part of a Nuclear Regulation Authority…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have also suggested that anthropogenic activities can promote reduced air dose rate (Saito et al, 2019;Nakama et al, 2019;Yoshimura et al, 2020), indicating their importance in controlling the radiocesium levels on the ground and their effect on variation and temporal change of the RF. Radiocesium activity was monitored in atmospheric aerosol samples collected at 11 sites for five months after the FDNPP accident as part of a Nuclear Regulation Authority…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In particular, we found that the effective half-life outside ERZ (0.22 y) was shorter than that inside the zone (0.29 y). Moreover, based on recent studies, the air dose rate outside ERZ decreased faster than inside ERZ, whereas the reduction was considered to be facilitated by anthropogenic activities (Saito et al, 2019;Nakama et al, 2019;Yoshimura et al, 2020). Therefore, anthropogenic activities may promote environmental remediation including atmospheric radiocesium concentration, suggesting that the anthropogenic activities possibly reduce the risk of inhalation radiation in the future.…”
Section: Rf Time Dependencementioning
confidence: 99%
See 1 more Smart Citation
“…We conducted eight-year measurements of atmospheric 134 Cs and 137 Cs in Fukushima city after the Fukushima Daiichi Nuclear Power Plant (FDNPP) accident that occurred in March 2011 to understand the time variations in and emission sources of 134 Cs and 137 Cs and to propose effective ways to reduce atmospheric radioactivity. Among the various radionuclides released to the environment, radio-Cs is particularly important due to its abundance in terrestrial ecosystems (the impacts of other nuclides were negligibly small 100 days after the accident; Yoshimura et al, 2020), long half-lives (2.06 y for 134 Cs and 30.17 y for 137 Cs), and bioaccumulation (accumulation in muscle tissues, with biological half-lives of 30-150 d;WHO, 2011). Radio-Cs forms aerosols in the air and is therefore efficiently deposited onto the ground surface via precipitation in addition to via dry deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Further study is required to determine if these numbers are significant, as thyroid cancer is a very common disease. Yoshimura et al (2020) report that there were significant differences between the types and amounts of radiation exposure at Chernobyl and Fukushima.…”
Section: Introduction/literature Reviewmentioning
confidence: 99%